Numerically Investigating the Effects of Slip and Thermal Convective on Nanofluid Boundary Layer Past a Stretching/shrinking Surface - N. Najib; N. Bachok; A. F. N. Rasedee; S. N. A. Salleh; W. N. W. Suhaimi (Lviv Polytechnic National University, 2024)
Indexed by Scopus